2022
DOI: 10.1161/jaha.122.027164
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Excess Aldosterone Promote Heart Failure With Preserved Ejection Fraction

Abstract: Background The pathobiology of heart failure with preserved ejection fraction (HFpEF) is still poorly understood, and effective therapies remain limited. Diabetes and mineralocorticoid excess are common and important pathophysiological factors that may synergistically promote HFpEF. The authors aimed to develop a novel animal model of HFpEF that recapitulates key aspects of the complex human phenotype with multiorgan impairments. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“… 30 Similarly, in mouse models of HFpEF, empagliflozin pre-incubation (4 h) but not acute treatment (3 min) was not only capable of reducing late I Na but also cellular proarrhythmia in ventricular cardiomyocytes in a CaMKII-dependent manner. 59 , 60 …”
Section: Discussionmentioning
confidence: 99%
“… 30 Similarly, in mouse models of HFpEF, empagliflozin pre-incubation (4 h) but not acute treatment (3 min) was not only capable of reducing late I Na but also cellular proarrhythmia in ventricular cardiomyocytes in a CaMKII-dependent manner. 59 , 60 …”
Section: Discussionmentioning
confidence: 99%
“…Many studies have also reported the effect of diabetes on heart failure. [54][55][56] Research has revealed that cardiometabolic damage is directly related to how diabetes affects heart failure. [57] Based on this, Halting the progression of diabetes is crucial for lowering the risk of heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities frequently associated with HFpEF are as follows: metabolic syndrome or its components (obesity, diabetes mellitus, hypertension), atrial fibrillation, diseases of the respiratory system (chronic obstructive pulmonary disease and sleep-disordered breathing), kidney disease, and anemia [37][38][39][40][41][42][43][44][45]. Glucose metabolism disorders and aldosterone excess favor both cardiac structural damage (cardiac hypertrophy and fibrosis leading to diastolic dysfunction and high ventricular filling pressures) and extracardiac comorbidities associated with HFpEF (diabetes mellitus with marked insulin resistance, severe obesity, vascular dysfunction, and pulmonary hypertension) [46]. There are recent data that show that excess accumulation of adipose tissue at the epicardial level is a risk factor for HFpEF.…”
Section: Etiologymentioning
confidence: 99%